Materials for hydrogen storage: structure and dynamics of borane ammonia complex - Parvanov, Vencislav M; Schenter, Gregory K; Hess, Nancy J; Daemen, Luke L; Hartl, Monika; Stowe, Ashley C; Camaioni, Donald M; Autrey, Tom (Dalton transactions : an international journal of inorganic chemistry, 2008)
The activation energies for rotations in low-temperature orthorhombic ammonia borane were analyzed and characterized in terms of electronic structure theory. The perdeuterated (11)B-enriched ammonia borane, (11)BD(3)ND(3), sample was synthesized, and the structure was refined from neutron powder diffraction data at 175 K. This temperature has been chosen as median of the range of previously reported nuclear magnetic resonance spectroscopy measurements of these rotations. A representative molecular cluster model was assembled from the refined geometry, and the activation energies were calculated and characterized by analysis of the environmental factors that control the rotational dynamics. The barrier for independent NH(3) rotation, E(a) = 12.7 kJ mol(-1), largely depends on the molecular conformational torsion in the solid-state geometry. The barrier for independent BH(3) rotation, E(a) = 38.3 kJ mol(-1), results from the summation of the effect of molecular torsion and large repulsive intermolecular hydrogen-hydrogen interactions. However, a barrier of E(a) = 31.1 kJ mol(-1) was calculated for internally correlated rotation with preserved molecular conformation. Analysis of the barrier heights and the corresponding rotational pathways shows that rotation of the BH(3) group involves strongly correlated rotation of the NH(3) end of the molecule. This observation suggests that the barrier from previously reported measurement of BH(3) rotation corresponds to H(3)B-NH(3) correlated rotation.